Analisis Karakter Gotong Royong Dalam Proyek Penguatan Profil Pelajar Pancasila (P5) Pada Siswa Kelas IV di SDN Tugurejo 03 Semarang - Sania, Neila Faridatus; Meganesia, Vinardita; Hidayah, Syilfa Ridhotul; Pebrian, Melina; Kiptiyah, Siti Maryatul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Character values are an important element in the Indonesian education curriculum. Various cases of decreasing character values that occur in the current young generation have prompted the government to design new steps, which are manifested in the Independent Learning Curriculum with the Strengthening Pancasila Student Profile Project. This research aims to analyze the character of mutual cooperation in the Project for Strengthening the Pancasila Student Profile (P5) among class IV students at SDN Tugurejo 03 Semarang. The method used is qualitative research with a descriptive approach. Data was collected through interviews, questionnaires and observations. The research results show that the implementation of P5 is able to improve students' mutual cooperation character. This can be seen from the value of the mutual cooperation character of class IV students at SDN Tugurejo 03 in the Strengthening Pancasila Student Profile project showing success with a percentage of 45% for the very good category, and 27% for the good category. Factors that contribute to the success of instilling the value of mutual cooperation lie in the activities of teachers and students during the Strengthening Pancasila Student Profile project. Overall, the results of these observations indicate that the value of the mutual cooperation character in the P5 project for class IV students at SDN Tugurejo 03 is relatively good.